Bio-inspired novel choline ester ionic liquid gel polymer electrolytes for safer lithium-ion batteries - Tommy Hoong Wy Lee; Phei Li Lau; Ianatul Khoiroh (Journal of Ionic Liquids)
The rise in lithium battery use has triggered concerns regarding safety due to flammable liquid electrolytes. Ionic liquids (ILs) present an alternative, offering low volatility and high stability. This study explores novel choline-based ILs incorporated into a polymer matrix to synthesise ionic liquid gel polymer electrolytes (GPEs). Structural confirmation via Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) spectroscopy verified successful synthesis, while the thermogravimetric analyzer (TGA) revealed their promising thermal stability. GPEs demonstrated remarkable flammability resistance compared to commercial separators. Electrochemical assessments, including electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), and galvanostatic charge-discharge (GCD), showcased high ionic conductivities and electrochemical stability. Transference numbers and dendrite growth analysis further underscored their excellent performance. Specifically, GPEs comprising 70 % propionyl choline bis(trifluoromethanesulfonyl)imide within a polymer matrix, poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP), exhibited exceptional conductivity and transference numbers, positioning them as strong candidates for safer and more efficient lithium-ion battery electrolytes.